ANALISIS KUANTITATIF ISOFLAVON TEMPE SECARA CEPAT DAN SEDERHANA MENGGUNAKAN METODE KROMATOGRAFI LAPIS TIPIS- DENSITOMETRI - Agustina Setiawati; Sri Hartati Yuliani; Enade Perdana Istyastono; Michael Rahardja Gani; Evy Fenny Veronica; Dina Christin Ayuning Putri; Reza Eka Putra; David Chandra Putra; Agnes Mutiara Kurniawan (Universitas Sanata Dharma, 2014)
Abstract: Rapid and simple quantitative analysis isoflavones tempe using densitometric TLC has been done. The mobile phase of the system was chloroform: methanol: ethylacetate (45: 5: 0.75). Thin layer chromatography was performed on aluminium TLC plates.Ascending distance of 1 μL sample was performanced 10 cm. Then the plate was scanned at 261 nm. A linear relationship obtained at 0.08 - 2 μg/spot with r= 0.9986. The LOD and LOQ of isoflavone were 0.014 μg/spot and 0.048 μg/spot. Genistein contained in tempe was 0.151± 0.005 % b/b. Keywords: tempe, isoflavon, TLC